Minimização da geração de resíduos sólidos domiciliares e de sua disposição em aterros sanitários: estudo de caso em condomínio vertical na cidade de João Pessoa-PB - Guedes, Natália de Souza (2020)
In view of the increase in the generation of household solid waste and, taking into account the polluting potential of this waste, the associated costs and the social aspect, measures aimed at guaranteeing the management of solid waste have become increasingly necessary. Environmental education practices, reduction, reuse, separation at source, recycling and composting are important tools to reduce the volume of RSD destined for landfills and, in turn, to send only rejected material to these deposits. Given the above, this research aimed to analyze, in a residential building located in the city of João Pessoa-PB, the impact of minimization strategies on the generation of household solid waste and the flow to be disposed of in landfills. Initially, the generation per capita of household solid waste in the building and the gravimetric composition of the waste generated were determined, after that the mobilization stage of the building population was initiated to implement reduction strategies, the practices adopted in the building were the selective collection, environmental awareness and composting. Finally, for the comparison between the average generation of household solid waste in the building without intervention and after the application of each strategy, the analysis of variance was used according to the graphic method GT-2, with a significance level of 5%. The results obtained show that the per capita generation rate of RSD of the building, calculated daily, before the application of the strategies was 0,490 kg/inhab.day and most of this waste is composed of organic matter (58.42%), while recyclable materials represent 26.59% of the waste generated. After the adoption of selective collection in the building, the amount of RSD sent to the landfill was 0.346 kg/inhab.day, with a reduction of 29% in relation to the generation rate without intervention. With the implementation of environmental awareness, this amount dropped to 0.329 kg/inhab.day, corresponding to a 32.85% reduction in waste sent to the landfill in the absence of strategies (0.490 kg/inhab.day) and a 5% reduction in relation to the per capita generation rate after selective collection (0.346 kg/inhab.day). With composting, the average rate of waste generation was 0.327 kg/inhab.day, resulting in a 33.26% reduction in relation to the generation rate calculated without any intervention (0.490 kg/inhab.day). However, in relation to the previous stage of environmental awareness (0.329 kg/inhab.day), the decrease in the tailings rate was only 0.61%. With the analysis of variance it was possible to observe that with the implementation of the selective collection, the environmental awareness (presentation) and the composting there was significant reduction in the per capita generation rate of the building's RSD that are effectively destined to the landfill.